A Short-Term Longitudinal Investigation of the Perceived Hookup Attitude of Gender-Specific Close Friends and Hookup Behavior - Yu, Ke; Zheng, Yong (Frontiers in Psychology, 2020)
Based on social learning theory and social norms theory, the current study examined two intervening variables (own attitude toward hookups, and affect following a recent hookup) as mediators of the association between perceived hookup attitudes of Chinese college students’ same-sex/opposite-sex close friends and number of hookup partners over six months. Chinese college students (N = 314) completed both Time 1 and Time 2 measures. The results of a path analysis showed that both perceived hookup attitudes of same-sex close friends and opposite-sex close friends were positively related to respondents’ own attitudes. Attitudes of respondents were positively related to positive affect and negatively related to negative affect. Only negative affect was negatively related to number of hookup partners at Time 2. Furthermore, students’ own attitudes toward hookups and negative affect following a hookup significantly mediated the association between perceived hookup attitudes of same-sex close friends and number of hookup partners over six months. These findings indicated that same-sex close friend injunctive norms were more strongly associated with future hookup behavior, as compared to opposite-sex friend injunctive norms. To better understand the relationship between peer norms and number of hookup partners, both students’ hookup attitudes and negative emotional response should be considered.